Determination of tetracycline, oxytetracycline and chlortetracycline residues in seafood products of Saudi Arabia using high performance liquid chromatography-Photo diode array detection - Fatimah Alanazi; Rawan Almugbel; Hadir M. Maher; Faten M. Alodaib; Nourah Z. Alzoman (Elsevier, 2021)
Residues of oxytetracycline, tetracycline and chlortetracycline in seafood products of Saudi Arabia were detected by using a simple, sensitive and rapid method via HPLC-PDA.The protein precipitation method that was used for sample extraction demonstrated high recoveries of OTC, TC and CTC. The limits of detection were 0.015 µg/g and 0.025,0.062 µg/g for all TCs in fish and shellfish, respectively. The limits of quantitation were 0.125 µg/g and 0.175 µg/g for all TCs in fish and shellfish, respectively. The method was precise and accurate since the RSD was less than 2%, while the % recovery was 95-105%. This study determined the occurrence of OTC, TC and CTC in seafood products that are sold in KSA's markets. The overall occurrence of these three medications in 249 seafood products was 24%(n = 60), while 15%(n = 37) exceeded the MRL. Thus, our recommendations are to enhance the monitoring of food production prior to marketing and to educate people regarding the proper disposal of antibiotics.